2001
DOI: 10.1128/mcb.21.5.1784-1794.2001
|View full text |Cite
|
Sign up to set email alerts
|

CAC3 (MSI1) Suppression ofRAS2G19V Is Independent of Chromatin Assembly Factor I and Mediated by NPR1

Abstract: Cac3p/Msi1p, the Saccharomyces cerevisiae homolog of retinoblastoma-associated protein 48 (RbAp48), is a component of chromatin assembly factor I (CAF-I), a complex that assembles histones H3 and H4 onto replicated DNA. CAC3 overexpression also suppresses the RAS/cyclic AMP (cAMP) signal transduction pathway by an unknown mechanism. We investigated this mechanism and found that CAC3 suppression of RAS/cAMP signal transduction was independent of either CAC1 or CAC2, subunits required for CAF-I function. CAC3 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 54 publications
(80 reference statements)
2
46
0
Order By: Relevance
“…One interpretation of these results is that the increased GCR rate of the cac1 single mutant and the cac1 cac3 double mutant may in part be due to the aberrant activity of subcomplexes of CAF-I containing CAC2 and possibly ASF1 (see below). It should be noted that other studies have also suggested that the different CAF-I subunits may also have distinct functions in addition to a shared function implied by their presence in the CAF-I complex (43)(44)(45)(46)(47), and defects in these different functions could also contribute to the differences between the effects of the cac1, cac2, and cac3 mutations seen here.…”
Section: Chromatin-assembly Factors Suppress Genome Instabilitymentioning
confidence: 48%
See 2 more Smart Citations
“…One interpretation of these results is that the increased GCR rate of the cac1 single mutant and the cac1 cac3 double mutant may in part be due to the aberrant activity of subcomplexes of CAF-I containing CAC2 and possibly ASF1 (see below). It should be noted that other studies have also suggested that the different CAF-I subunits may also have distinct functions in addition to a shared function implied by their presence in the CAF-I complex (43)(44)(45)(46)(47), and defects in these different functions could also contribute to the differences between the effects of the cac1, cac2, and cac3 mutations seen here.…”
Section: Chromatin-assembly Factors Suppress Genome Instabilitymentioning
confidence: 48%
“…Interestingly, induction of a dominant-negative CAC1 in mammalian cells induced phosphorylated histone H2Ax foci (31). It should also be noted that other studies have suggested that CAC1-CAC3 all seem to have distinct functions in addition to a common function (43)(44)(45)(46)(47), and it is known that a portion of CAC3 does not copurify with the CAF-I complex (49,70). Thus, it is also possible that these differences in function could contribute to the differences in the effects of the cac1, cac2, and cac3 mutations seen here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise regulatory mechanism via which Msi1 functions in the Ras/ cAMP-signaling pathway in budding yeast is not completely understood, several lines of evidence indicate that Msi1 operates either between the Cyr1 adenylyl cyclase and protein kinase A (PKA) or downstream of PKA. MSI1 overexpression suppresses the heat shock sensitivity caused by the deletion of two phosphodiesterases, Pde1 and Pde2, or by an activated TPK2 allele but not by the deletion of the Bcy1 regulatory subunit of PKA, suggesting that Msi1 downregulates Ras/cAMP signaling by inhibiting PKA in a Bcy1-dependent manner (21,46). Supporting this, Msi1 does not inhibit intracellular cAMP synthesis (46).…”
mentioning
confidence: 59%
“…Interestingly, however, Msi1 also does not affect total PKA catalytic activity, indicating that Msi1 may affect the subcellular localization of PKA (46). In addition, Msi1 was found to negatively regulate the Ras/cAMP pathway by sequestering and inactivating the Npr1 serine/threonine kinase, which is known to promote or antagonize the ubiquitin-mediated degradation of several nutrient transporters (21). Indeed, MSI1 overexpression phenotypes are strikingly similar to those of an npr1⌬ mutant.…”
mentioning
confidence: 87%